Pembelajaran Fiqih di Pondok Pesantren Daarul Amiin Islamic Boarding School - Dinda Husnainah Sobirin; Erik Wilgian Ramadhan; A. Yasin Nahrowi (Universitas Nusantara PGRI Kediri, 2024)
This study aims to describe the implementation of Fiqh learning at the Daarul Amiin Islamic Boarding School. This study uses a descriptive qualitative method with interview, observation, and documentation data collection techniques. The results of the study indicate that Daarul Amiin Islamic Boarding School uses a modern and applicable Fiqh curriculum and learning methods. The Fiqh curriculum at Daarul Amiin Islamic Boarding School integrates the national curriculum with the pesantren curriculum. The Fiqh learning methods used at Daarul Amiin Islamic Boarding School include the book reading method, the lecture method, and the demonstration method. Evaluation of Fiqh learning at Daarul Amiin Islamic Boarding School is carried out practically. The conclusion of this study is that Daarul Amiin Islamic Boarding School has succeeded in implementing modern and applicable Fiqh learning. This is indicated by the use of a Fiqh curriculum and learning methods that are in accordance with the needs of the students, as well as the results of the Fiqh learning evaluation which show that the students have good abilities in understanding and practicing Fiqh material.